Solving common development challenges with React Native applications : solutions for handling three common application development challenges - Lebensold, Jonathan (O'Reilly, 2017)
"How do I manage my layout and styles? How do I get data from a web server? How do I perform simple animations? These are three sets of challenges that face virtually every app developer today. This course will solve these challenges, making it possible for you to create your native apps in a faster and easier way. You'll learn about the React Native classes for handling style sheets, getting hardware information, and communicating with the web. You'll also explore React Native's open source ecosystem and build a simple GraphQL client, as well as examine the lesser known features of React that enable you to build sophisticated interpolations and manage animations. Learners should have basic web programming experience using JavaScript."--Resource description page